Ethical dispute control in Islamic banking relationship - Adamu, Idris Yahaya; Abdul Rahim, Ahmad Khilmy; Hamed, Abu Bakar (2017)
This paper examines application of ethical practice in conflict management process in Islamic banking relationship.The paper used interpretive qualitative research, based on current practice of Jaiz Islamic bank in Nigeria.Data were gathered from Jaiz Islamic bank staff, through semi structured interview.The findings show that, Jaiz Islamic bank managers uses Sulh (conciliation and compromise) more than Mushawarah (consensus building) approach, once disagreements occur.If conflict escalates, they preferably employ non-binding arbitration process using experts like Fatawal-mufti and or CBN than arbiter judge (court annexed).Managers expresses their opposition to any form of court litigation, rather, they prefer out of court settlement to settle dispute, due to resultant effect of court litigation on business relationship continuity.Jaiz Islamic bankers therefore, are found to be innovative in conflict management in all customer related issues.The study contributes to literature of dispute control by effectively resolving dispute issues at less cost.